Low cost and earth abundant iron based magnetic cooling materials - Low, Qi Fan (2018)
Magnetocaloric materials with good magnetocaloric properties are getting more attention and popularity due to its ability to perform cooling at room temperature. This poses as a potential replacement for the current technology of vapour compression cooling systems. However, most magnetocaloric materials that possess good properties at room temperature are made up of rare earth metals, which are expensive and geographically limited. Hence, there is an urgent need to develop new magnetocaloric materials that are of common and commercial available materials. In this report, iron-based alloys of Fe75-xCrxAl25, where x = 19, 23 and 25, were fabricated using arc melting and planetary ball milling. The magnetic properties, size and composition of Fe75-xCrxAl25 alloys were investigated and characterised using a Vibrating Sample Magnetometer, Transmission Electron Microscope and via X-ray Diffraction. Afterwards, a ferrofluid was synthesised using the iron-based alloys. It was then tested for its cooling ability in a thermomagnetic convection system. Using Fe50Cr25Al25 ferrofluid, a maximum cooling rate of 5.4oC was attained with the input power load of a 5W heat load, with a volume percentage of 0.8% v/v and 0.25 Tesla magnetic field strength. Future work in this research project can focus on increasing the content of chromium in the alloys to further reduce Curie temperature to room temperature while maintaining the suitable magnetization. Work should also be done to increase the stability of the ferrofluid.